Gustav: CPU accounting for small-sized grid infrastructures. (1st January 2012) - Barbera, Roberto; Giorgio, Emidio; Hwang, Soonwook; Ricciardi, Gianni M.
Geographically distributed computational infrastructures, based on the grid paradigm, are increasingly coming out of the research sphere where they originated, presenting themselves as a candidate for low-effort business solution for accessing and using vast computing infrastructures, much larger than those that small-to-medium enterprises can usually afford building 'in house'. In such scenario, accounting and billing systems play a key role, as any business model cannot opt out of instruments showing who has used how many resources in a given period of time. For this reason, several grid middleware accounting systems have been developed in the last years. Such accounting systems are generally targeted for large-sized infrastructures. However, sometimes different needs arise, especially for smaller grid sites participating in large distributed infrastructures. Gustav aims to fulfil some of these requirements in a simple and reliable way, and could be considered as an alternative approach to CPU accounting for grid sites.